THE EFFECTIVENESS OF THE KLAMPID NEW GENERATION (KNG) IN POPULATION ADMINISTRATION SERVICES IN WONOREJO VILLAGE, RUNGKUT - Firmansyah, Yoga Ardianto; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The research aims to evaluate how the KNG, an innovation developed by the Surabaya City Population and Civil Registration Office, simplifies online civil registration services for the community. Method: A descriptive qualitative approach was applied, with data collected through observation, interviews, documentation, and literature review. The analysis was guided by Sutrisno’s (2010) five indicators of effectiveness: program understanding, target accuracy, timeliness, achievement of objectives, and tangible changes. Results: Findings reveal that while KNG has streamlined civil registration processes, public understanding remains limited, particularly among those with low digital literacy, which constrains independent utilization of the system. Ineffectiveness in user comprehension directly impacts the timeliness and accessibility of services. Novelty: This study contributes by applying Sutrisno’s multidimensional framework to assess an IT-based public service innovation at the village level, emphasizing the critical role of public awareness campaigns, continuous training, and digital literacy empowerment in ensuring the sustainable effectiveness of e-government services.